Only the Rye Derived Part of the 1BL/1RS Hybrid Centromere Incorporates CENH3 of Wheat - Karimi-Ashtiyani, Raheleh; Schubert, Veit; Houben, Andreas (Frontiers in Plant Science, 2021)
The precise assembly of the kinetochore complex at the centromere is epigenetically determined by substituting histone H3 with the centromere-specific histone H3 variant CENH3 in centromeric nucleosomes. A chromosome 1B reconstructed in wheat by centric misdivision from two wheat-rye centric translocations is known to carry a hybrid wheat-rye centromere. The resulting hybrid (dicentric)centromere is composed of both wheat and rye centromeric repeats. As CENH3 is a marker for centromere activity, we applied Immuno-FISH followed by ultrastructural super-resolution microscopy to address whether both or only parts of the hybrid centromere are active. Our study demonstrates that only the rye-derived centromere part incorporates CENH3 of wheat in the 1BL/1RS hybrid centromere. This finding supports the notion that one centromere part of a translocated chromosome undergoes inactivation, creating functional monocentric chromosomes to maintain chromosome stability.